The Prevention of Occupational Heat Stress in Sugarcane Workers in Nicaragua—An Interpretative Phenomenological Analysis - Pacheco-Zenteno, Felipe; Glaser, Jason; Jakobsson, Kristina; Weiss, Ilana; Arias-Monge, Esteban; Gyllensten, Kristina (Frontiers in Public Health, 2021)
Background: Chronic kidney disease of non-traditional origin (CKDnt) is an ongoing epidemic that has taken the lives of tens of thousands of people in Mesoamerica, also affecting other tropical geographies. Occupational heat stress, which will increase worldwide as climate change persists, has been identified as a primary trigger of kidney injury and reduced renal function. At Nicaragua's largest sugarcane mill, the water, rest, and shade (WRS) intervention has proven to reduce the risk of heat stress and kidney injury effectively as assessed by the research and policy NGO La Isla Network (LIN) and their academic partners, who have worked with the sugar mill to improve the design of their intervention system. However, discrepancies between intervention design and implementation have been found. This study explores the perceptions of the WRS intervention in the company from the perspective of positions responsible for the workers' environment and heat stress prevention implementation. Methods: A qualitative design was used in the study. Twenty-one key informants of low and middle management, field assistants, and two members from LIN took part in the study. Semi-structured interviews were used to collect the data. Interviews' transcriptions were analyzed using interpretative phenomenological analysis (IPA). Results: Four main themes were developed in the analysis of the data: “A worthwhile struggle,” “Culture of care”, “Traditional production culture Vs. Culture of care,” and “The importance of the formalization of care.” Each theme contained sub-themes, all of which were further discussed in the light of organizational psychology. Conclusion and Implications: Discretionary differences resulting in low and middle management prioritizing production over health protection appeared to relate to a fair part of the implementation challenges and indicate that more efforts are needed to align operations' production and health goals. Education enhancement might be necessary, while further focus on health metrics for performance assessment might offer an opportunity to level perceived incentives and value of health and production.